HUBUNGAN PENGETAHUAN KESEHATAN PRIBADI DENGAN PERILAKU HIDUP SEHAT PADA SISWA - Udi Sahudi (Universitas Majalengka, 2017)
AbstractThe purpose of this study was to determine the existence of the personal health level of students in class III-VI of SD Negeri Bonang I, Panyingkiran District, Majalengka Regency, 2014/2015 Academic Year. The population in this study were students of SD Negeri Bonang I, Panyingkiran District, Majalengka Regency in the 2014/2015 Academic Year, totaling 204 students. While the samples in this study were students of class III-VI totaling 135 students. This research uses quantitative descriptive methods. The collection method used was a survey technique using a questionnaire or questionnaire and interviews. The data obtained were analyzed using percentage descriptive techniques. Based on the results of the study obtained an average personal health score of students of SD Negeri Bonang I, Panyingkiran District, Majalengka Regency, 2014/2015 Academic Year of 103.3 with a percentage of 77.9% and included in both categories. Referring to the results of the study, it turns out that the personal health of students of Bonang I Elementary School, Panyingkiran District, Majalengkas Regency is already good.Keyword: Personal health knowledge, healthy living behaviors. AbstrakTujuan penelitian ini adalah untuk mengetahui keberadaan tingkat kesehatan pribadi siswa kelas III-VI SD Negeri Bonang I Kecamatan Panyingkiran Kabupaten MajalengkaTahun Pelajaran 2014/2015. Populasi dalam penelitian ini adalah siswa SD Negeri Bonang I Kecamatan Panyingkiran Kabupaten Majalengka Tahun Pelajaran 2014/2015, sebanyak 204 siswa. Sedangkan yang dijadikan sampel dalam penelitian ini siswa kelas III-VI sebanyak 135 siswa. Penelitian ini menggunakan metode deskriptif kuantitatif. Metode pengumpulan yang digunakan adalah teknik survei dengan menggunakan angket atau quesioner dan wawancara. Data yang diperoleh dianalisis dengan menggunkaan teknik deskriptif persentase. Berdasarkan hasil penelitian diperoleh rata-rata skor kesehatan pribadi siswa SD Negeri Bonang I Kecamatan Panyingkiran Kabupaten MajalengkaTahun Pelajaran 2014/2015 sebesar 103,3 dengan persentase 77,9% dan termasuk kategori baik. Mengacu dari hasil penelitian,ternyata kesehatan pribadi siswa SD Negeri Bonang I Kecamatan Panyingkiran Kabupaten Majalengkasudah baik.Kata Kunci: Pengetahuan kesehatan pribadi, perilaku hidup sehat